Systematic Literature Review: Work readiness of vocational high school graduates in facing the industrial 4.0 era - Ina Nurjanah; A. Ana; Alias Masek (Faculty of Engineering, Universitas Negeri Yogyakarta, 2022)
The Industrial Era 4.0 requires Vocational High School (SMK) graduates to have high capabilities and competitiveness in facing global job competition. Therefore, every graduate is expected to have Work Readiness that is in accordance with the demands of the industry and the world of work. There are many studies examining aspects of Work Readiness that graduates must possess in the industry 4.0 era. So, it is necessary to review journal papers that discuss the Work Readiness of SMK graduates facing the Industrial 4.0 era. The method used in this study is Systematic Literature Review of journal papers published from 2016-2021. The findings of this study are: first, 13 research focuses were found as a result of mapping journals that are interrelated each other covering topics about graduates, students, dimensions, industry, curriculum, factors, experience, training, workers, skills, employers, employability, and soft skills. Second, 10 Work Readiness that must be possessed by graduates, namely readiness to adopt technology, communication skills, collaboration skills, adaptability, analytical and problem solving skills, critical thinking skills, innovativeness, independence, creativity, and curiosity. Third, the readiness to adopt technology in facing digitalization is the most priority aspect of Work Readiness needed for SMK graduates in the Industrial Revolution 4.0 era. The findings of this study expected to be basic reference on developing SMK Curriculum in the context of Industrial 4.0 era. So that the SMK graduates will have good work readiness that fulfill the demands of Industry.